Characteristics, primary sources and secondary formation of water-soluble organic aerosols in downtown Beijing - Q. Yu; Q. Yu; J. Chen; J. Chen; W. Qin; W. Qin; S. Cheng; S. Cheng; Y. Zhang; Y. Zhang; Y. Sun; Y. Sun; et al. (Atmospheric Chemistry and Physics, 2021)
Water-soluble organic carbon (WSOC) accounts for a large proportion of aerosols and plays a critical role in various atmospheric chemical processes. In order to investigate the primary sources and secondary production of WSOC in downtown Beijing, day and night fine particulate matter (PM2.5) samples in January (winter), April (spring), July (summer) and October (autumn) 2017 were collected and analyzed for WSOC and organic tracers in this study. WSOC was dominated by its moderately hydrophilic fraction and showed the highest concentration in January and comparable levels in April, July and October 2017. Some typical organic tracers were chosen to evaluate the emission strength and secondary formation of WSOC. Seasonal variation of the organic tracers suggested significantly enhanced formation of anthropogenic secondary organic aerosols (SOAs) during the sampling period in winter and obviously elevated biogenic SOA formation during the sampling period in summer. These organic tracers were applied into a positive matrix factorization (PMF) model to calculate the source contributions of WSOC as well as its moderately and strongly hydrophilic portions. The secondary sources contributed more than 50 % to WSOC, with higher contributions during the sampling periods in summer (75.1 %) and winter (67.4 %), and the largest contributor was aromatic SOC. In addition, source apportionment results under different pollution levels suggested that controlling biomass burning and aromatic precursors would be effective to reduce WSOC during the haze episodes in cold seasons. The impact factors for the formation of different SOA tracers and total secondary organic carbon (SOC) as well as moderately and strongly hydrophilic SOC were also investigated. The acid-catalyzed heterogeneous or aqueous-phase oxidation appeared to dominate in the SOC formation during the sampling period in winter, while the photochemical oxidation played a more critical role during the sampling period in summer. Moreover, photooxidation played a more critical role in the formation of moderately hydrophilic SOC, while the heterogeneous or aqueous-phase reactions had more vital effects on the formation of strongly hydrophilic SOC.